Extensões e aplicações do modelo de tributação indireta ótima de Deaton - Badagnan, Thaisa França (2016)
It is known in the literature on optimal indirect taxes the existence of a trade off between allocative eficiency and equity in the determination of tax rates on consumption. Among the various papers published in this area, the Deaton (1977) stands out to present na alternative to traditional models in resolving this trade-off, compared to only two types of agents, the middleincome agent and income agent socially representative. Despite this innovative feature at work now cited, the model proposed by Deaton (1977) has been very little explored in the literature. In view of these arguments, the main objective of this thesis is to study the optimal indirect taxation model Deaton (1977) in three respects. First, it establishes conditions under which it is possible to obtain an explicit formula for the vector of optimal rates of Deaton (1997). The essential condition to ensure the validity of the formula is one of the goods should be selected for which the rate is fixed in advance. The result is an equation that can be solved by any software that performs mathematical calculations matrix equations. Using the formula obtained were estimated optimal indirect tax rates for all federal units of Brazil. The estimation was proposed for nine groups of goods, such as: processed foods, food in natura, the food of cesta básica, clothing, cleaning products, medicines, toiletries, alcohol and telecommunications services. The POF / IBGE 2008/2009 data were used. Among the results, we can highlight the allowance for alcoholic beverages in most federal units. This is a result commonly found in the literature on optimal indirect taxation. Finally, it proposes a way to estimate the aversion parameter inequality of Atkinson (1970) from the model Deaton (1977). Using the equation of great indirect rate proposed in Chapter 2, applies a method of reverse engineering, getting a way to estimate the parameter that measures the degree of inequality aversion associated with a given tax structure. The proposed method is used to estimate the inequality aversion measures for each state of Brazil using the results obtained in the second part, together with the tax rates (ICMS) in force in 2009.